2022
DOI: 10.1111/1467-8268.12669
|View full text |Cite
|
Sign up to set email alerts
|

Bigger or better? The effect of public spending on happiness in Africa

Abstract: The aim of this paper is to assess the effect of government spending on happiness in 39 African countries from 2006 to 2018. The neoclassical view predicts a positive effect, while public choice theory predicts the opposite.The results obtained using the Generalized Method of Moment reveal that public spending has no direct effect on happiness in Africa. However, public spending positively affects happiness in the poorest countries of Africa. Furthermore, governments can improve the happiness of African popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…Even in the absence of direct terrorist attacks, Boly and Kéré (2023) discovered that growth in a country can be adversely affected by terrorism spillover or complementarity with military spending. Fambeu et al (2022) showed that public spending has no direct effect on happiness in Africa. Raifu et al (2022) utilized the ARDL technique to show that in Nigeria, military spending has a short-term positive effect on reducing unemployment, but in the long run, it exacerbates unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even in the absence of direct terrorist attacks, Boly and Kéré (2023) discovered that growth in a country can be adversely affected by terrorism spillover or complementarity with military spending. Fambeu et al (2022) showed that public spending has no direct effect on happiness in Africa. Raifu et al (2022) utilized the ARDL technique to show that in Nigeria, military spending has a short-term positive effect on reducing unemployment, but in the long run, it exacerbates unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xi,t ${X}_{i,t}$ est une matrice de variables de contrôle, sélectionnées sur la base de littérature sur les déterminants de la croissance. Ces variables comprennent, notamment l'investissement, l'ouverture commerciale, le capital humain, la population, les indices de stabilité politique, de contrôle de la corruption et du terrorisme (Becker et al, 1999; Bayale, 2018; Bayale, Traoré, Diarra, et al, 2022; Dunne et al, 2005; Fambeu et al, 2022; Fan & Zhang, 2008; Hanushek & Woessmann, 2010; Papagni el al., 2021; Rodríguez & Rodrik, 2000; Rodrik, 2008; Sala‐I‐Martin, 1996).…”
Section: Méthodologie Et Donné De L'étudeunclassified
“…The study found that the impact of public debt on economic growth is moderated by the quality of the institutions and the proportion of productive expenditure. Fambeu et al (2022) studied the effect of government spending on happiness in 39 African countries from 2006 to 2018. They found that public spending positively affects happiness in the poorest countries of Africa.…”
Section: Review Of Literaturementioning
confidence: 99%
“…One major issue that is attracting the attention of scholars and policymakers globally, and in sub‐Saharan African (SSA) countries, in particular, is the rapid increase in the level of public debts over the last few decades (Akram, 2016; Beqiraj et al, 2018; Carner et al, 2021; Fambeu et al, 2022; Kassouri et al, 2021; Law et al, 2021; Makun, 2021; Napo, 2022; Olaoye, 2022a, 2022b; Owusu‐Nantwi & Erickson, 2016; Sennoga & Balma, 2022; Wang et al, 2021). In the last two decades, the total public debt for SSA increased from an average of 27% of gross domestic product (GDP) in 2010 to over 56% in 2018.…”
Section: Introductionmentioning
confidence: 99%